The Patient's Brain : the neuroscience behind the doctor-patient relationship. - Benedetti, Fabrizio (OUP Oxford, 2010)
There is a vast literature on what has often been called the doctor-patient relationship, patient-provider interaction, therapist-patient encounter, and such like. However, it is thanks to recent advances within neuroscience, that we now find ourselves in a much better position to be able to describe and discuss the biological mechanisms that underlie the doctor-patient relationship. For example, we now know that different physiological and biochemical mechanisms take part incomplex functions, like trust, hope, empathy and compassion, which are all key elements in the therapist-patient encount.